2006
DOI: 10.1099/jmm.0.46183-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxicity and genetic variation among clinical Staphylococcus aureus isolates in Jordan

Abstract: A total of 100 Jordanian clinical Staphylococcus aureus isolates was analysed for the presence of the enterotoxin genes sea, seb, sec, sed and see using multiplex PCR. Twenty-three isolates (23 %) were potentially enterotoxigenic. The prevalence of sea, sec and sea plus sec among the total clinical isolates was 15, 4 and 4 %, respectively. None of the isolates harboured sed, seb or see genes. S. aureus isolates were subjected to DNA fingerprinting by randomly amplified polymorphic DNA (RAPD) analysis to test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 22 publications
8
21
2
Order By: Relevance
“…However, these results appeared to be completely different from results reported by Peles et al [45] who reported that only 15% of S. aureus isolated from milk samples in Hungary harbored at least one toxin gene indicating the low prevalence of toxin genes in non-pathogenic S. aureus isolated from milk samples. However, the results appeared different from those reported by Naffa et al [23] who showed that only 23% of the clinical isolates exhibited at least one toxin gene. The exceptionally high prevalence of toxin genes among the tested isolates in this study could be due to the nature of the tertiary hospitals in which most of the patients are referred from primary health care establishments.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, these results appeared to be completely different from results reported by Peles et al [45] who reported that only 15% of S. aureus isolated from milk samples in Hungary harbored at least one toxin gene indicating the low prevalence of toxin genes in non-pathogenic S. aureus isolated from milk samples. However, the results appeared different from those reported by Naffa et al [23] who showed that only 23% of the clinical isolates exhibited at least one toxin gene. The exceptionally high prevalence of toxin genes among the tested isolates in this study could be due to the nature of the tertiary hospitals in which most of the patients are referred from primary health care establishments.…”
Section: Discussioncontrasting
confidence: 56%
“…The statistical program SPSS, version 20 (IBM, USA) was used for the analysis. A 0.17 and 0.30 similarity was calculated for AluI and CfoI respectively, using the method of Naffa et al [23], and was used as a discriminating threshold to define homologous clusters. Table 4 shows that 158 S. aureus isolates (63.2 %) exhibited resistance to oxacillin, while only 154 of the isolates (61.6%) were resistant to cefoxitin.…”
Section: Statistical Analysis and Phylogenetic Tree Developmentmentioning
confidence: 99%
“…There are frequent reports of prevalence of S. aureus in extensively used traditional cheeses [5, 6]. Staphylococcal Enterotoxins (SEs), the main causatives for food poisoning, are a group of single chain, low molecular mass proteins and are produced during all phases of growth [7]. Based on serological classification, to date several SEs have been recognized such as SEA, SEB, SEC, SED, and SEE [8].…”
Section: Introductionmentioning
confidence: 99%
“…Random amplification of polymorphic DNA (RAPD PCR) has been applied extensively to distinguish different isolates of S. aureus [11, 12]. However, there is little information on the RAPD method for typing S. aureus strains isolated from dairy products.…”
Section: Introductionmentioning
confidence: 99%